2001
DOI: 10.1783/147118901101195038
|View full text |Cite
|
Sign up to set email alerts
|

Family planning provision in the Trent health region: Is it accessible to school aged teenagers?

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…4 A number of studies have suggested that factors restricting access to contraceptive services for young people (such as limited provision outside school hours) exist, and that accessibility should be improved. 5,6 Services that are available to young people through weekday lunchtimes, evenings and weekends, for instance, would improve the accessibility of condoms to young people. 7 One possible strategy for improving access to condoms outside current family planning clinic (FPC) opening times is to increase access to condom vending machines (CVMs) for young people.…”
Section: Introductionmentioning
confidence: 99%
“…4 A number of studies have suggested that factors restricting access to contraceptive services for young people (such as limited provision outside school hours) exist, and that accessibility should be improved. 5,6 Services that are available to young people through weekday lunchtimes, evenings and weekends, for instance, would improve the accessibility of condoms to young people. 7 One possible strategy for improving access to condoms outside current family planning clinic (FPC) opening times is to increase access to condom vending machines (CVMs) for young people.…”
Section: Introductionmentioning
confidence: 99%
“…Anonymous young persons service has not been a popular concept until recently, and is still unavailable in most parts of the country, partly because of cost implications 14 . A study in the Trent region showed that opening hours of the family planning services are unsuitable for youngsters attending school 15 . Recent research has shown that comprehensive community based programmes, which have links with local schools, optimize contraceptive compliance.…”
Section: O N T R a C E P T I V E U S A G Ementioning
confidence: 99%
“…In terms of the accessibility of services, findings suggest that services are not always accessible to young people as for example, they are sometimes only open during school hours (43). There have been many studies which have used attitudinal measures to determine the acceptability of services, and it seems fair to conclude that young people favour drop-in services that are informal, confidential and welcome young people aged under 16 years of age (42,44,45).…”
Section: What Aspects Of Service Are Important?mentioning
confidence: 99%